SISTEM INFORMASI PADA PONDOK PESANTREN AL-QOSIM MUARO JAMBI: web-based, al-qosim boarding school, information system. - Suana, Irma (JURNAL AKADEMIKA, 2018)
During this time the data processing system in the Al-Qosim Islamic Boarding School information system is still done manually. Where in the data processing system previously experienced many obstacles in the delivered of reports to the leadership, and felt inaccurate and efficient in the processing of data processing at the Muaro Jambi Al-Qosim Islamic Boarding School. Therefore, the authors identified, evaluated the problems and obstacles that occur so that can be proposed to improve it by developing it in the form of research with the title "information system at the al-qosim Islamic boarding school muaro jambi". making this information is done by means of data collection, analysis, design, implementation up to the testing of information systems, research objects in this case the Muaro Jambi Al-Qosim Islamic Boarding School. The information system is created by using the PHP progress language. The final result of this program is the information system of Islamic Boarding Schools that can be used to facilitate Pondok employees in processing student data and as a medium of information for santri parents regarding their child academic.